Unforgivable blackness [videorecording (DVD)] : the rise and fall of Jack Johnson - Burns, Ken, 1953-; David, Keith; Jackson, Samuel L. (PBS Home Video, 2005)
The in-depth and intimate story of one of the most important African Americans to live in the first half of the 20th century. Tells the story of Jack Johnson, who was the first African American boxer to win the most coveted title in all of sports - Heavyweight Campion of the World. Includes his struggles in and out of the ring and his desire to live his life as a free man.